2010
DOI: 10.3928/01477447-20100826-11
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Injection of Hyaluronic Acid Following Arthroscopic Partial Meniscectomy of the Knee

Abstract: The short-term recovery period post-arthroscopic meniscectomy is characterized by pain and impaired function most likely related to the irrigation of synovial fluid from the knee intraoperatively. Consequently, along with removal of harmful debris, the irrigation fluid dilutes the hyaluronic acid layer covering the joint tissues. Hyaluronic acid contributes to the homeostasis of the joint environment and is an important component of synovial fluid and cartilage matrix. Hence, the instillation of hyaluronic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…One included RCT reported that hyaluronic acid treatment was capable of substantially alleviating pain and symptoms within 2 days after arthroscopic anterior cruciate ligament reconstruction (18). Another RCT also reported that statistically significant pain reduction was found one week postoperatively in arthroscopic surgery (26). In our meta-analysis, hyaluronic acid was revealed to significantly reduce pain on motion in knee arthroscopy, but had no influence on pain control 2, 6 and 12 weeks after the arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…One included RCT reported that hyaluronic acid treatment was capable of substantially alleviating pain and symptoms within 2 days after arthroscopic anterior cruciate ligament reconstruction (18). Another RCT also reported that statistically significant pain reduction was found one week postoperatively in arthroscopic surgery (26). In our meta-analysis, hyaluronic acid was revealed to significantly reduce pain on motion in knee arthroscopy, but had no influence on pain control 2, 6 and 12 weeks after the arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 54%
“…There were similar characteristics between the hyaluronic acid group and the control group at baseline. One RCT reported knee arthroscopy for anterior cruciate ligament reconstruction (18), 2 RCTs reported knee arthroscopy for meniscus tear (26,27), 2 RCTs reported arthroscopic debridement for knee osteoarthritis (19,21), and 1 RCT reported arthroscopic knee joint lavage, or in combination with cartilage debridement (20). (20,27).…”
Section: Literature Search Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Early viscosupplementation in arthroscopic partial meniscectomy was found to have conflicting results and a possible improvement in short-term pain is not showed in all level I studies [178][179][180] . Different studies on viscosupplementation after ACL reconstruction evidenced inflammation, swelling and pain reduction only in the immediate post-operative period, without any difference in the longterm 69,181,182 .…”
Section: Ha After Knee Arthroscopymentioning
confidence: 99%
“…4 During the first 4 weeks, patients with viscoseal following arthroscopic meniscectomy achieve better pain control and reduced analgesic use than controls do. 16,17 Nonetheless, the sample sizes in the 2 studies were small (40 and 56 patients). Our sample size was also small.…”
Section: Discussionmentioning
confidence: 99%